Morphophysiological Study of Kecapi (Sandoricum koetjape Merr.) Seedlings Against Different Artificial Light Spectra and Intensities - Defitrianida, Asyhuriyah Wardah; Poerwanto, Roedhy; Hapsari, Dhika Prita; Matra, Deden Derajat (Department of Agronomy and Horticulture, IPB University, 2025)
Kecapi (Sandoricum koetjape Merr.) is a tropical fruit species that belongs to the Meliaceae family. Kecapi trees require 5-7 years to produce fruit when grown from seeds, necessitating efforts to accelerate their growth, including through the modification of light. This research aimed to study kecapi’s morphological, physiological, and anatomical responses to light spectra and intensities from light-emitting diodes. The experiment was designed using a two-factor, completely randomized design (CRD), namely LED light spectrum (white and purple) and light intensity (2 and 4 lights). The result showed that morphological and vegetative growth were significantly affected under the high-intensity purple LED treatment. The low-intensity purple LED treatment increased stomatal conductance and chlorophyll-b synthesis. The transpiration rate was highest under the high intensity white LED treatment. Low-intensity white LED treatment only increased the abaxial stomatal aperture. As the intensity increased, it also increased N-Total content but decreased micronutrient levels in the leaves.